Development of Alginate Composite Microparticles for Encapsulation of Bifidobacterium animalis subsp. lactis - Marko Vinceković; Lana Živković; Elmira Turkeyeva; Botagoz Mutaliyeva; Galiya Madybekova; Suzana Šegota; Nataša Šijaković Vujičić; Anđela Pustak; Tanja Jurkin; Marta Kiš; Sanja Kajić (Gels, 2024)
The probiotic bacterium Bifidobacterium animalis subsp. lactis BB-12 (BB-12) was encapsulated in two composites, alginate/agar and alginate/agar/casein. The network structure and physicochemical properties of these composites are influenced by complex interactions, including hydrogen bonding, electrostatic forces between biopolymers, calcium ions, and the encapsulated bacteria. The composites demonstrated a granular surface, with the granules being spatially oriented on the alginate/agar/BB-12 surface and linearly oriented on the alginate/agar/casein/BB-12 surface. They possess a highly organized microparticle structure and exhibit viscoelastic solid-like behavior. The alginate/agar/BB-12 composite showed higher storage modulus, shear stress, and shear strain values, indicating enhanced stability in various physical environments. Both composites displayed good thermal stability, aligning with their rheological properties, confirming their well-ordered structures. Despite differences in composite structures, the release mechanism of bacteria is governed by Fickian diffusion through the composite matrix. Based on physicochemical properties, the alginate/agar/casein composite is recommended for dairy product fermentation, while the alginate/agar composite seems more suitable for oral use. These findings provide new insights into the interactions between bacterial cultures and alginate composite ingredients.